Validity of force generation and speed movement during bench press in male wrestlers: practical applications - Feriche, B.; Calderon-Soto, C.; Chirosa, I.; Chirosa, L. J.; Escobar, R.; Olea, F.; Mariscal, M.; Bonitch-Gongora, J.; Bonitch, J.; Galilea, P.; Riera, J.; Gutierrez, J. A.; et al. (Archivos de medicina del deporte, 2008)
The ability to develop explosive movements with heavy and light loads is crucial in Olympic Wrestling disciplines. In order to analyze these manifestations of upper body strength in wrestlers and to determine the functional profile adjusted to the demands of high competition, we examine the force-velocity relationship (F-V) as a fundamental part of the control and planning of the training in wrestlers. Sixteen Olympic trained wrestlers participated in this study. The protocol consisted of a bench press test (concentric phase) of increasing loads (F-V curve), analyzing power (P), force (F), and velocity (V), with an electronic dynamometer (Real power Pro of Globus), at different loads and the variables related to the maximum power (MP). The evaluation was done at the beginning of the special preparation phase. Results showed a power curve with a marked zone at the top. The MP observed were of 6.71±1,14 W/Kg, and they were obtained at speed of 1,06±0,12 m/s and at 44,21±6,75% of RM. The maximum strength values (Fmax) were of 1,06±0,22 Kg/Kg of mc. All of these results showed deficiencies with respect to other wrestling disciplines (10.06 ± 3.17 W/kg of PM vs 1.41 ± 0.49 m/s of V and 1.28 ± 0.16 Kg/Kg of mc of RM). We can conclude that the F-V curve analyzed is a valid procedure in planning and control of strength training. The results display a medium-low MP level in the study group at a low load. Two further strength training objectives remain for these subjects: an increase in optimal Fmax values and the improvement of the MP in heavy loads.